Laser interstitial thermal therapy of lung lesions near large vessels: a numerical study. (1st May 2023) - Effat, Andrew; Bernards, Nicholas; Gregor, Alexander; Young, Edmond W K; Yasufuku, Kazuhiro; Weersink, Robert A
Abstract: Objective. Laser interstitial thermal therapy (LITT) is an evolving hyperthermia-based technology that may offer a minimally invasive alternative to inoperable lung cancer. LITT of perivascular targets is challenged by higher risk of disease recurrence due to vascular heat sinks, as well as risk of damage to these vascular structures. The objective of this work is to examine the impact of multiple vessel parameters on the efficacy of the treatment and the integrity of the vessel wall in perivascular LITT. Approach. A finite element model is used to examine the role of vessel proximity, flow rate, and wall thickness on the outcome of the treatment . Main result . The simulated work indicates that vessel proximity is the major factor in driving the magnitude of the heat sink effect. Vessels situated near the target volume may act as a protective measure for reducing healthy tissue damage. Vessels with thicker walls are more at risk of damage during treatment. Interventions to reduce the flow rate may reduce the vessel's heat sink effect but may also result in increased risk of vascular wall damage. Lastly, even at reduced blood flow rates, the volume of blood reaching the threshold of irreversible damage (>43 °C) is negligible compared to the volume of blood flow throughout the treatment duration. Significance. This investigative simulation yields results that may help guide clinicians on treatment planning near large vessels.